Contribuição ao estudo da evidenciação das normas contábeis aplicadas às concessionárias de rodovias públicas - Yamada, Walter Nobuyuki (2008)
The objective of this essay is to analyse the aplication of norms and procedures on accounting of public road concessions, especially, of those of road exploration. The interest in researching of such public road concessions is due to the fact of the same that they have worked with long term contracts something from 20 to over 25 years, as well as to analyse the accounting treatment spend on to the cost of concession and amortization. The disclosure of financial statements of public service concessions suggests standarded basic procedures and norms, in order to support administrators and generators to show information that can present a better result search. Those companies show the profile of being based on the law, which conducts the researching of legal fundaments. The resource used was of that documentation researching, through bibliografical search and documents of the update laws, texts such as: articles on newspapers, specialize magazines related to the theme on focus. The researching shows the lack of consistency in reason of the absence of standarded norms to the sector may present distortions on comparative analysis of the estate of this activity, in contrast with to the adoption of non consisting procedures, about of the accounting treatment spend on to the cost of concession and amortization. This essay shows the need and urgency of regulating the norms and accountability procedures in order to support administrators and generators to take better decisions, so the economic scenery waves a growth on new roadways given to private companies by the concession process